Clostridioides (Clostridium) Difficile in Food-Producing Animals, Horses and Household Pets: A Comprehensive Review - Kachrimanidou, Melina (Microorganisms, 2019)
Clostridioides (Clostridium) difficile is ubiquitous in the environment and is also considered as a bacterium of great importance in diarrhea-associated disease for humans and different animal species. Food animals and household pets are frequently found positive for toxigenic C. difficile without exposing clinical signs of infection. Humans and animals share common C. difficile ribotypes (RTs) suggesting potential zoonotic transmission. However, the role of animals for the development of human infection due to C. difficile remains unclear. One major public health issue is the existence of asymptomatic animals that carry and shed the bacterium to the environment, and infect individuals or populations, directly or through the food chain. C. difficile ribotype 078 is frequently isolated from food animals and household pets as well as from their environment. Nevertheless, direct evidence for the transmission of this particular ribotype from animals to humans has never been established. This review will summarize the current available data on epidemiology, clinical presentations, risk factors and laboratory diagnosis of C. difficile infection in food animals and household pets, outline potential prevention and control strategies, and also describe the current evidence towards a zoonotic potential of C. difficile infection.